A Uniquely Complex Mitochondrial Proteome from Euglena gracilis. (5th April 2020) - Hammond, Michael J; Nenarokova, Anna; Butenko, Anzhelika; Zoltner, Martin; Dobáková, Eva Lacová; Field, Mark C; Lukeš, Julius
Abstract: Euglena gracilis is a metabolically flexible, photosynthetic, and adaptable free-living protist of considerable environmental importance and biotechnological value. By label-free liquid chromatography tandem mass spectrometry, a total of 1, 786 proteins were identified from the E. gracilis purified mitochondria, representing one of the largest mitochondrial proteomes so far described. Despite this apparent complexity, protein machinery responsible for the extensive RNA editing, splicing, and processing in the sister clades diplonemids and kinetoplastids is absent. This strongly suggests that the complex mechanisms of mitochondrial gene expression in diplonemids and kinetoplastids occurred late in euglenozoan evolution, arising independently. By contrast, the alternative oxidase pathway and numerous ribosomal subunits presumed to be specific for parasitic trypanosomes are present in E. gracilis . We investigated the evolution of unexplored protein families, including import complexes, cristae formation proteins, and translation termination factors, as well as canonical and unique metabolic pathways. We additionally compare this mitoproteome with the transcriptome of Eutreptiella gymnastica, illuminating conserved features of Euglenida mitochondria as well as those exclusive to E. gracilis . This is the first mitochondrial proteome of a free-living protist from the Excavata and one of few available for protists as a whole. This study alters our views of the evolution of the mitochondrion and indicates early emergence of complexity within euglenozoan mitochondria, independent of parasitism.